Rediscovery of Jasminum parkeri Dunn, an endemic and endangered taxon from the western Himalaya, India - Lal, Brij; Datta, Arunava; Parkash, Om; Deosharan, Rakesh (Biodiversity: Research and Conservation, 2015)
The present article deals with the rediscovery of Jasminum parkeri Dunn (Oleaceae) collected from its type locality after a lapse of about 100 years. J. parkeri is a highly endangered and narrowly endemic taxon restricted to a small pocket in the remote mountain area of Chamba district, Himachal Pradesh in the western Himalaya, India. In order to facilitate identification of this species, the plant description along with a brief history of its discovery, affinity with the other taxa of Jasminum, ecological notes, and pictures are provided. Subsequently, possibility of cultivation of this species in ex-situ conditions is also discussed.